Legal Protection for Victims of Online Gender-Based Violence (Cyber-Based Violence) - Alip Rahman; Anom Sutrisno; Lita Martia; Feri Wangi (PT Publikasiku Academic Solution, 2024)
Online gender-based violence is a serious problem that negatively impacts victims physically, psychologically and socially. This research aims to analyze the legal protection of victims of cyber-based violence in Indonesia, focusing on existing regulations and their implementation. The method used in this research is a normative research method with a juridical-analytical approach, where data is collected through a literature study of relevant laws and regulations, legal documents, and previous research related to online gender-based violence. The results show that Law No. 12 of 2022 on the Crime of Sexual Violence provides a strong legal basis for victim protection, including the right to assistance, temporary protection, and recovery. In addition, regulations regarding the removal of content involving victims are an important step in reducing further impact. However, this research also found challenges in law enforcement, public awareness, and training of law enforcement officers that need to be strengthened in order for victim protection to be implemented effectively. This research is expected to contribute to improving the understanding and effectiveness of legal protection for victims of online gender-based violence in Indonesia.